PENGEMBANGAN SISTEM PEMINJAMAN INVENTARIS BERBASIS WEB MENGGUNAKAN PENDEKATAN USER-CENTERED DESIGN - Alia Agisna; Rizki Hikmawan (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Inventory management in education is often still carried out traditionally using physical forms, which results in various problems such as delays in data entry, duplicate data, and difficulties in tracking the status of borrowed items. This study aims to design a web-based inventory borrowing system that can improve efficiency and transparency in asset management. The system was created using a user-centered design (UCD) approach to ensure that user needs are the basis for designing the system. A system evaluation was conducted on 12 participants consisting of 10 students and 2 inventory management staff using the System Usability Scale (SUS), User Experience Questionnaire (UEQ), and semi-structured interviews to evaluate user experience. In addition, interviews were also conducted to gain deeper insight into users' views on the developed system. The test results showed that the system received a SUS score of 85.25, which is included in the "Very Good" category and exceeds the global usability average of 68. The UEQ analysis showed that all dimensions of user experience provided positive results, with scores above 0.8. These findings indicate that the developed system offers a good level of usability and a satisfactory user experience. This system facilitates a more organized inventory borrowing process.